Synthesis and crystallization of zeolite A - Mat, Ramli (Faculty of Chemical & Natural Resources Engineering, 1993)
Zeolite A is a crystalline aluminosilicate. represented by the formula Na12[(AlO2)12(SiO2)12] 27H2O. It has a wide range of application as ion exchangers. One of these is in a detergent builder, suggested in the 1970’s to replace the phosphate builder for environmental reasons. The crystalline material is usually prepared by combining sources of silica, alumina and alkali to form an aluminosilicate gel. The product obtained is depend on the composition of the reaction mixture and reaction condition. This paper outlines some of the factors affecting zeolite crystallization.